Ca12[Mn19N23] and Ca133[Mn216N260]: Structural Complexity by 2D Intergrowth. Issue 36 (6th August 2018) - Ovchinnikov, Alexander; Bobnar, Matej; Prots, Yurii; Borrmann, Horst; Sichelschmidt, Jörg; Grin, Yuri; Höhn, Peter
Abstract: Two new calcium nitridomanganates, Ca12 [Mn19 N23 ] ( P 3, a =11.81341(3) Å, c =5.58975(2) Å, Z =1) and Ca133 [Mn216 N260 ] ( P 3 ‾, a =39.477(1) Å, c =5.5974(2) Å, Z =1), were obtained by a gas–solid reaction of Ca3 N2 and Mn with N2 at 1273 K and 1223 K, respectively. The crystal structure of Ca12 [Mn19 N23 ] was determined from high‐resolution X‐ray synchrotron powder diffraction data, whereas single‐crystal X‐ray diffraction was employed to establish the crystal structure of the Ca133 [Mn216 N260 ] phase, which classifies as a complex metallic alloy (CMA). Both crystal structures have 2D nitridomanganate layers containing similar building blocks but of different levels of structural complexity. Bonding analysis as well as magnetic susceptibility and electron spin resonance measurements revealed that only a fraction of the Mn atoms in both structures carries a localized magnetic moment, while for most Mn species the magnetism is quenched as a result of metal–metal bond formation. Abstract : The calcium nitridomanganates Ca133 [Mn216 N260 ], which classifies as complex metallic alloy (CMA) CMA phases, and Ca12 [Mn19 N23 ] have complex 2D nitridomanganate layers with only a fraction of the Mn atoms in both structures carrying localized magnetic moments, while for the remaining Mn atoms the magnetism is quenched through metal–metal bond formation.